An Effective Life–Sex–Emotions Course for Taiwanese Adolescents on Health Perceptions: A Cohort Study - Chao, Kuo-Yu; Cheng, Wei (Frontiers in Public Health, 2021)
Aim: Adolescence is a time of transition from childhood to adulthood, when young people go through a number of vital physical and psychological developments. It is surprising yet unfortunate that the number of teenage suicide deaths and teenage infections of gonorrhea have increased over the years, becoming serious public health concerns in Taiwan. The aim of this study was to investigate whether a course of Life-Sex-Emotional Education was effective in enhancing teenagers’ understanding of adolescence, and was helpful to improve their attitudes toward life and sex. Material and methods: Grade 5 to 9 pupils who participated in the course were given pre- and post-tests of PILSEE (Perception Index of Life-Sex-Emotional Education) questionnaire from September 2017 to June 2020 in Taiwan. Results: A total of 10506 questionnaires completed by pupils in both pre- and post-tests were collected. PILSEE score for each question was 3.76-4.68 (SD range=.674-1.211) in the pre-test, and 4.34-4.74 (SD range=.596-1.001) in the post-test. The overall score was 86.86 (SD=10.83) in the pre-test and 92.62 (SD=10.30) in the post-test. There was statistically significant difference by pair t test, t=55.46 (p<0.01). From the qualitative analysis, self-esteem, and the understanding of adolescence as well as of media influences appeared to have increased from feedback from the participating pupils. Conclusion: The results of the study showed that the course of Life-Sex-Emotional Education was effective in improving the participants’ understanding of adolescence, life value, sex, and associated issues.